Rotation in rectangular and circular reinforced elastomeric bearings resulting in lift-off. (15th August 2019) - Van Engelen, Niel C.
Abstract: Rotation is an important design consideration in reinforced elastomeric bearings (a composite of an elastomer and steel or fiber reinforcement). In certain circumstances, an applied rotation may overcome the hydrostatic compressive pressure due to the applied axial load. If this occurs, a tensile stress will develop in bonded bearings, or lift-off (i.e. the loss of contact between the bearing and the supports) will occur in unbonded bearings. In this paper, analytical solutions are derived to predict the initiation of lift-off or development of tensile stress in infinite strip, rectangular and circular pads including the compressibility of the elastomer and the extensibility of the reinforcement – parameters which are often ignored. The unbonded infinite strip and rectangular pad geometries are further investigated for the impact of rotations exceeding lift-off on the instantaneous geometry and moment-rotation relationship of the bearing. Due to the complexity of the analytical solutions, simplified geometry-specific approximations and graphs are derived that are appropriate for design applications. It is shown that the current code methodology may contain significant error in predicting the initiation of lift-off in unbonded applications or the introduction of a tensile stress in bonded applications.